4 Day in dry immersion reproduces partially the aging effect on the arteries as observed during 6 month spaceflight or confinement - Danielle Greaves (Nature Portfolio, 2021)
Abstract The objectives of this study were to determine whether 4 days of dry immersion (DI) induced similar arterial aging as spaceflight and to test the impact of thigh cuffs. Eighteen subjects underwent DI; nine wore thigh cuffs. Cardiac and arterial targets were assessed by ultrasound. No significant differences were found between the groups. The left ventricle volume, stroke volume (SV), and ejection fraction decreased with DI (p < 0.001). Carotid distensibility reduced (p < 0.05), carotid to femoral arterial tree became stiffer in 33% of the subjects, and femoral artery intima media thickness increased (p < 0.05). A reduction in plasma volume is likely to have caused the observed cardiac changes, whereas the arterial wall changes are probably best explained by hypokinesia and/or environmental stress. These changes are similar but lower in amplitude than those observed in spaceflight and mimic the natural aging effect on earth. The daytime-worn thigh cuffs had no acute or chronic impact on these arterial-focused measurements.